THE WELL-FORMED HABITUS OF REFUGEE’S CHILDREN - Fathya Diana Maritza; Yohanes Tuaderu (STBA Prayoga Padang, 2022)
Abstract Habitus is an action that is influenced by the surrounding environment that results in practices. This article will show the process of forming a well-formed habitus and the influence of a well-formed habitus on the social life of refugees children. This article uses the sociological theory by Pierre Felix Bourdieu by using several concepts such as Habitus, Capital, and Field. In this research, the writer used qualitative methods in the form of words, phrases, sentences, and paragraphs and also used descriptive methods in the form of descriptive analysis. The results showed that the process of forming a well-formed habitus in refugees children resulted in the habit of fondness for learning and the habit of using English which developed into a habitus for refugees children; love of gaining knowledge, diligence in studying, and the ability to speak English fluently. In addition, thisresearch also shows the influence of the well-formed habitus of children in the Dadaab refugee camp on their social life; a wider and more profitable relationships as well as being superior in material and immaterial wealth which determines the structure and social status of refugee children.